Percobaan Ekonomi untuk Mengkaji Pengaruh Informasi serta Jumlah Penjual dan Pembeli dalam Transaksi Pasar - Supriyadi, Edy (Bina Nusantara University, 2010)
Perfect competition (PPS) is the most ideal market structure because this market system is considered will ensure the realization of activities producing goods and services with very high efficiency compared to other market structures such as monopoly. Due to its benefits for sellers and buyers, economists often wish for the creation of perfect competition. In the pattern of transactions in everyday life, there are many market transactions commonly encountered, such as decentralized systems (DT), and Double Auction (DA). This paper presents the use of experimental methods to study the characteristics of both systems the transaction is in a